Preliminary development of a bystander intervention scale for depression and the examination of socio-demographic correlates amongst Singapore university students - Wei Jie Ong; Jue Hua Lau; Edimansyah Abdin; Shazana Shahwan; Janrius Chong Min Goh; Gregory Tee Hng Tan; Ellaisha Samari; Kian Woon Kwok; Mythily Subramaniam; Siow Ann Chong (BMC Psychology, 2021)
Abstract Background Despite peer involvement having a positive impact on help-seeking behavior, there is a lack of a scale quantifying the possibility of an individual intervening upon noticing peers who show signs of depression. The aims of this study were to (1) develop a bystander intervention scale for depression that assesses the likelihood of university students intervening when a peer shows signs of depression based on the theory of bystander intervention, (2) identify the underlying factors contributing to the behavior, and (3) explore the socio-demographic correlates of the scale. Methods The proposed scale, the Bystander Intervention Scale for Depression (BISD), is a 17-item self-reported questionnaire that was developed based on existing bystander intervention theory and inputs from mental health experts. Data was collected as part of a larger study to evaluate the effectiveness of an anti-stigma intervention amongst university students from a local university. A total of 392 participants were recruited. Exploratory factor analyses were performed to identify the underlying factor structure. Multiple linear regressions were conducted to explore the socio-demographic correlates of the scale. Result Four key factors were identified for the proposed scale: (1) Awareness of depression among peers; (2) Vigilance towards possible symptoms of depression; (3) Knowledge on how to intervene; (4) Acceptance of responsibility to intervene. Having experience in the mental health field was associated with all factors while having family members or friends with mental illness was associated with all factors except for knowledge on how to intervene. Students of older age were associated with higher vigilance towards possible symptoms of depression and knowledge on how to intervene. Those of non-Chinese ethnicity were associated with acceptance of responsibility to intervene. Conclusion This study provides a preliminary tool to assess bystander intervention in depression amongst university students. This study identifies sub-groups of the student population that require more education to intervene with depressed peers and also informs the development of future strategies.